1981
DOI: 10.1159/000182175
|View full text |Cite
|
Sign up to set email alerts
|

Uremic ‘Toxins’ and Blood Platelet Carbohydrate Metabolism

Abstract: The effect of various small and middle molecular substances on blood platelet glycolysis was studied in vitro. Creatinine inhibited glucose utilization only at a concentration of 30 mg/dl; no effect of urea was found. o-Hydroxyphenolic acid and guanidinosuccinic acid, which were supposed to interfere with platelet function, inhibited glucose utilization at concentrations found in plasma of patients with chronic renal failure (CRF). Inhibitor of glucose utilization (IGU) peptide of middle molecular weight was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Inhibition of glycolysis by IGU [13] probably accounts for the marked inhibition that has been shown in all the tests of platelet function, for IGU has not been shown to alter cellular oxidative processes [2]. IGU interferes with glycolysis at the level of phosphofructokina.se [1], and it has been shown in erythrocytes that this inhibition is non competitive [8],…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of glycolysis by IGU [13] probably accounts for the marked inhibition that has been shown in all the tests of platelet function, for IGU has not been shown to alter cellular oxidative processes [2]. IGU interferes with glycolysis at the level of phosphofructokina.se [1], and it has been shown in erythrocytes that this inhibition is non competitive [8],…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance of the activation of plate let factor 3 [10] and of the aggregation [7] and adhesion [6] of platelets has been described by several groups and has been attributed by some to uremic toxins, such as phenolic compounds or guanidinosuccinate [9], Adenosine triphosphate plays an important role in platelet participation in hemostasis, and of course, glucose is the main substrate for adenosine triphosphate synthesis. Thus, inhibition of glycolysis in various tissues [3] includ ing the platelets [13] by phenolic acids, guanidinosuccinic acid, and the middle molecular 'inhibitor of glucose utiliza tion' (IGU) could explain the functional platelet defect of uremia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported that the increased con centrations of the so-called 'middle molecules' (MMs) as postulated in the middle molecule hypothesis [7], which would normally be removed by the kidneys, may contribute significantly to the uremic syndrome [8][9][10][11][12][13][14][15][16][17]. It seems highly probable that MMs are peptidic substances [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many authors have reported the increased concentrations of peptides in uremic blood and some of which have toxicity [8][9][10][11][12][13][14][15][16][17], In addition, it is well known that the blood levels of many peptide hormones are elevated in patients with uremia [6], Recently, Massry and Goldstein [34] have stressed that parathyroid hormone is a major uremic toxin. Abiko et al [35][36][37] have isolated the tripeptide (His-Gly-Lys), the heptapeptide (His-Pro-Ala-Glu-AsnGly-Lys) and the pentapeptide (Asp-Leu-Trp-Gln-Lys) from the UF of blood obtained from uremic patients.…”
mentioning
confidence: 99%